Implementation Of The Islamic Law Transformations' Rule (Taghayyur Ahkam) DuringG Covid-19 Pandemic In The Perspective Of Majelis Tarjih MUujammadiyyah In Indonesia - Fajar Rachmadhani; Mualimin Mochammad Sahid; Ahmad Wifaq Mokhtar (USIM Press, 2024)
VOL. 10 NO. 1 (2022) Page(108-117)